A flexibilização das relações de trabalho da enfermagem no Hospital Universitário da Universidade Federal do Espírito Santo (1988-1998) - Alves, Sheila Maria Parreira (2013)
A study on the flexibilisation of labour relationships in Health, and its consequences on the nursing work in a university hospital between the years of 1988 and 1998. Describing labour in the dynamics of capitalism, it contextualises the flexibilisation of labour relationships and its repercussions on the public service since the 1990 State Reform, concentrating on the university hospitals. The methodology of thematic oral history is adopted, resulting in a social historical study, with the analysis of oral testimonials being used to comprehend the perception by the social body of the nurse staff of a university hospital, of the meaning of the flexibilisation of labour relationships; the conclusion is that this process, embodied mainly by the outsourcing used for replacement of workers, has resulted in disruption and discontinuity of the services held by the hospital, in staff turnover, and in difficulties of administration due to the coexistence within the same organisational environment of different bonds, wages and advantages, causing losses to the institution’s functions of assistance, teaching, and mostly to the workers which are affected by social insecurity and the deterioration of the working conditions. The Brazilian Company for Healthcare Services, which assumes administration of the university hospitals with a new proposal of management, is identified as a still unknown alternative for the institution’s workforce, thus providing motivation for new studies.